2017
DOI: 10.1093/sleep/zsx099
|View full text |Cite
|
Sign up to set email alerts
|

Recorded and Reported Sleepiness: The Association Between Brain Arousal in Resting State and Subjective Daytime Sleepiness

Abstract: The present study contributes to the validation of VIGALL. Despite the considerable interval between ESS and EEG assessment dates, the strength of ESS-VIGALL association approximates prior ESS-Multiple Sleep Latency Test results. In this light, VIGALL might constitute an economical choice for the objective assessment of daytime sleepiness in large cohort studies. The discriminative power to identify disorders of hypersomnolence, however, remains to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…This finding is in line with the study findings from Olbrich et al [11] and more recently by Jawinski et al [28], who demonstrated a gradual change of ANS activity in different states of brain arousal in 15-min resting EEG data. Most importantly, these gradual ANS changes were present in most cases within each 30-min time block.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with the study findings from Olbrich et al [11] and more recently by Jawinski et al [28], who demonstrated a gradual change of ANS activity in different states of brain arousal in 15-min resting EEG data. Most importantly, these gradual ANS changes were present in most cases within each 30-min time block.…”
Section: Discussionsupporting
confidence: 93%
“…Further results show that objective measured sleepiness was significantly associated with the reported likelihood of having fallen asleep during EEG recordings and was almost significantly associated with subjective daytime sleepiness. These results are in line with recent findings of a study by Jawinski et al (56), which investigated the association between recorded and reported sleepiness in a population-based cohort study including 10,000 randomly selected inhabitants of Leipzig, Germany. They found moderate correlations between objective sleepiness parameters and the reported likelihood of having fallen asleep.…”
Section: Discussionsupporting
confidence: 92%
“…Physiological data were collected and processed, as previously described [26]. All EEGs were recorded according to the same standardized operating procedure.…”
Section: Physiological Data Collection and Processingmentioning
confidence: 99%
“…By incorporating information on the spectral composition and cortical distribution of EEG activity, VIGALL enables the computerized assessment of EEG-vigilance as an indicator of brain arousal in the resting state. The algorithm has been validated in functional imaging studies [22][23][24], against parameters of the autonomous nervous system [25,26], and against subjective ratings [26]. Beyond conventional DSM and ICD disorder categories, VIGALL may constitute one tool to identify etiologically more homogenous psychiatric patient groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation